2005
DOI: 10.1007/s10499-005-0615-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Synthetic Pyrethroid Cypermethrin on the Common Carp (Cyprinus carpio L.) Embryos and Larvae

Abstract: In this study, the toxic effects on the embryos and larvae of the common carp were used as a model to investigate the synthetic pyrethroid pesticide, cypermethrin, which contaminates aquatic ecosystems. Data obtained from the cypermethrin acute toxicity tests were evaluated using the Probit Analysis Statistical Method. The control and eight test experiments were repeated five times. The number of dead embryos significantly increased in response to cypermethrin concentrations 0.0001, 0.001, 0.01, 0.1, 1, 2, 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…We observed increased mortality dependent on concentration and duration of exposure. Similarly, acute toxicity tests of deltamethrin and cypermethrin in embryos and larvae of common carp have shown concentration-dependent decreases in hatching success (Koprucu and Aydin 2004;Aydin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased mortality dependent on concentration and duration of exposure. Similarly, acute toxicity tests of deltamethrin and cypermethrin in embryos and larvae of common carp have shown concentration-dependent decreases in hatching success (Koprucu and Aydin 2004;Aydin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…En especial los peces tienen ciertas deficiencias enzimáticas para hidrolizar los piretroides, además su sistema nervioso es muy sensible y tienen una baja capacidad de metabolizar y eliminar insecticidas (Bradbury et al 1986, Viran et al 2003, Aydin et al 2005.…”
Section: Discussionunclassified
“…Tramujas et al (2006) did not report signiϐicant change on zebraϐish (Danio rerio) hatching rate after exposure to sublethal concentrations of Deltamethrin. Aydin et al (2005) reported mortality of common carp (Cyprinus carp) alevins after 12 hours of exposure to Cypermethrin.…”
Section: Reproductive Parametersmentioning
confidence: 99%
“…Such insecticides tend to be toxic to ϐish and other aquatic organisms. Several products containing Pyrethroids are classiϐied as 'limited use pesticides', by the Environmental Protection Agency, due to their toxicity to ϐish (Aydin et al 2005, Saha & Kaviraj 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation